Keadilan Sebagai Hasil Kerja Kolektif Pemerintah-Masyarakat Dalam Memberantas Korupsi dan Ketidakadilan Hukum di Indonesia - Emanuel Katarino Mbeo (Studia Philosophica et Theologica, 2023)
The focus of this paper is on the concept of "Justice as a Government-Society Collectivity in Eradicating Corruption and Legal Injustice in Indonesia" viewed from Plato's point of view. This paper departs from the desire that justice must be upheld as fairly as possible. Because justice is a primary need that must be met in order to achieve universal welfare, for all Indonesian citizens, not for particular ones. This paper aims to explore the fundamental concepts of justice, then relate them to the reality of the Indonesian nation. Everyone has a desired version of justice to apply. This paper has its own uniqueness, namely taking the concepts of justice from the book “Plato-The Republic”, and this book is the main source. The method used is the method of literature and case studies that are relevant to the concept of justice offered. The cases presented are cases related to legal injustice and corruption which are more in line with the focus of this paper. The author finds that to achieve justice, there must be collaboration between the government and society. Collaboration means that there is dialogue to determine a universal decision. Dialogue produces decisions that are right on target and acceptable to the public. One-sided decision-making can even be detrimental to many parties and the emergence of various irregularities, one of which is corruption. Unilateral decisions that give rise to injustice in making and applying the law